La importancia de aplicar estrategias afectivas en la inclusión de niños con necesidades educativas especiales en el inicial II del centro de educación globitos de colores en el año lectivo 2016 - 2017 - Cabada López, Olga Alejandrina (2016)
The main objective of this research is to motivate teachers to apply affective strategies to handle four-years old children with special educations needs from the center Globitos de Colores with special educational needs. The study of inclusion also has its place as a main objective, which is to promote equal rights within an equitable society where respect for the diversity of cultures, customs, religion and a number of prejudices the human being above as barriers to coexistence in harmony, same proposed overthrow through affective strategies founded on the basis of the expression of feelings using a series of tools gestural, corporal, expressed from the first years of life that are the most relevant to foster human values which will grow up learning in a comprehensive manner, a thematic plan are taken into consideration for the development of the affective handling of teaching with five indicators taken as example with objectives and activities.........